FISHERS OF THE CORDED WARE CULTURE IN THE EASTERN BALTIC. Issue 1 (12th June 2020) - Piličiauskas, Gytis; Kluczynska, Grażyna; Kisielienė, Dalia; Skipitytė, Raminta; Peseckas, Kęstutis; Matuzevičiūtė, Simona; Lukešová, Hana; Lucquin, Alexandre; Craig, Oliver E.; Robson, Harry K.
ABSTRACT: Between 2800 and 2400 cal BC pastoralists from Central Europe migrated into the eastern Baltic paving the way for the Corded Ware Culture (CWC), and a new type of economy, animal husbandry. Traditionally the CWC people were viewed as highly mobile due to the lack of substantial traces of dwellings and material culture at settlement sites; they were reliant on an economy based on animal husbandry as demonstrated by zooarchaeological and stable isotopic evidence. However, this paradigm is beginning to shift. Here, we present new AMS radiocarbon ( 14 C) measurements, pollen and macrobotanical data from sediment samples and a portable fish screen, as well as technological, molecular and isotopic data obtained from ceramic vessels from three CWC sites in the eastern Baltic. Overall, our results indicate a de‐Neolithisation process undergone by some CWC groups, particularly in lacustrine and coastal ecotones, and a shift to hunting, gathering and fishing.